Efek Residu Pemberian Tricho-Kompos Jerami Padi Terhadap Pertumbuhan Produksi Sawi Hijau (Brassica juncea. L) - Edison Anom (Universitas Riau, 2008)
The objective of this research was to obtain the best dosage of paddy straw compost as residual effect from the first planting toward growth and production of green mustard at the second planting. The experimental research was carried out in duration of 3 months using Completely Block Randomized Design (CBRD) with 5 treatments and 4 replications. The treatments were the application of paddy straw Tricho-compost of o ton/ha, 10 tons/ha, 15 tons/ha, 20 tons/ha, and 25 tons/ha. Parameters observed were plant height (cm), leaf area (cm2), number of leaf (piece), root length (cm), fresh weight of plant (g) and consumable fresh weight of the plant (g). Deta obtained were analyzed by anova and continued by Duncant New Multiple Range Test (DNMRT) at 5% level. The result of this research showed that application of paddy straw Tricho compost at 20 tons/ha dosage for the first planting gave the best effect for the growth and production of green mustard at second planting. There was an increase of green mustard growth an production at the second planting.